PERAN PEMERINTAH DESA DALAM PENANGGULANGAN KEJAHATAN (Studi Di Desa Nowa Kecamatan Woja Kabupaten Dompu) - Ma’arij, Aman; Gufran, Gufran (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Crime is a bad act, derived from the word evil which means very bad, very bad, very bad, while juridically crime is defined as an act that violates the law or is prohibited by law in the first problem research what is the cause of crime in Indonesia? Nowa Village, Woja District, Dompu Regency and how is the role of the nowa village government in overcoming crimes such as gambling, conflict and other crimes. The purpose of this study was to find out how the role of the village government in overcoming crime in the village of Nowa, Woja sub-district, Dompu district and the factors that influence the occurrence of crime in Nowa Village, Woja District, Dompu Regency, this study used empirical research methods using the approach of legislation, sociology and cases. The results showed that the role of the village government in tackling crime in the nowa village was to carry out socialization at the hamlet level and strengthen coordination between agencies, both from the village government and law enforcement officers (police) and the factor that influenced the occurrence of crime in nowa village was the level of youth promiscuity. , Brutal Archery, Rampant Distribution of Alcohol and Drugs, Legal Gambling, and Brawls Between Youth.